Nuclear Nox4-Derived Reactive Oxygen Species in Myelodysplastic Syndromes. (26th February 2014) - Guida, Marianna; Maraldi, Tullia; Beretti, Francesca; Follo, Matilde Y.; Manzoli, Lucia; De Pol, Anto
Abstract : A role for intracellular ROS production has been recently implicated in the pathogenesis and progression of a wide variety of neoplasias. ROS sources, such as NAD(P)H oxidase (Nox) complexes, are frequently activated in AML (acute myeloid leukemia) blasts and strongly contribute to their proliferation, survival, and drug resistance. Myelodysplastic syndromes (MDS) comprise a heterogeneous group of disorders characterized by ineffective hematopoiesis, with an increased propensity to develop AML. The molecular basis for MDS progression is unknown, but a key element in MDS disease progression is the genomic instability. NADPH oxidases are now recognized to have specific subcellular localizations, this targeting to specific compartments for localized ROS production. Local Nox-dependent ROS production in the nucleus may contribute to the regulation of redox-dependent cell growth, differentiation, senescence, DNA damage, and apoptosis. We observed that Nox1, 2, and 4 isoforms and p22phox and Rac1 subunits are expressed in MDS/AML cell lines and MDS samples, also in the nuclear fractions. Interestingly, Nox4 interacts with ERK and Akt1 within nuclear speckle domain, suggesting that Nox4 could be involved in regulating gene expression and splicing factor activity. These data contribute to the elucidation of the molecular mechanisms used by nuclear ROS to drive MDS evolution to AML.